Development and validation of an HPLC-DAD method for Rapid quantification of vasicine in Adhatoda vasica leaves and commercial products. Issue 8 (August 2022) - Velichkova, S.; Theunis, M.; Naessens, T.; Pieters, L.; Foubert, K.
Abstract: Leaves from Adhatoda vasica Nees, Acanthaceae (synonym Justicia adhatoda L.) have been widely used in traditional medicine for their beneficial effect in the treatment of respiratory diseases. Vasicine, the main quinazoline alkaloid in A. vasica, has been linked to its medicinal properties. The purpose of this work was to develop and validate a reliable analytical method for the quantification of vasicine in A. vasica leaves and commercially available products. For this purpose, a high-performance liquid chromatography method coupled to diode array detection (HPLC-DAD) was used. After optimization of the extraction process and the HPLC conditions, linearity, precision, accuracy, and specificity were checked. During the validation, six commonly available food supplements and dosage forms were tested using the validated method. The calibration model was found to be linear in the concentration range of 5.125–205 μg/mL. The average vasicine content at different concentration levels was 0.99 g/100 g with an RSD% of 0.05%. The average recovery was found to be 102.3% with an RSD of 4.3%. Additionally, it was confirmed that the validated method was still precise and accurate for quantifying vasicine in other matrices like the tested preparations. In summary, the validated method was suitable for the determination of vasicine in leaves of Adhatoda vasica, as well as for investigating the quality and the prescribed intake of several commercial products. Abstract : Adhatoda vasicaLeavesVasicineMethod developmentMethod validationHPLC-DAD